2013
DOI: 10.1111/j.1365-4632.2012.05815.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leishmaniasis: new dermoscopic findings

Abstract: Yellow tears, white starburst-like patterns and salmon-colored ovoid structures seem to appear specifically in CL lesions. In geographical areas in which CL is common, dermoscopy may be utilized as a useful diagnostic tool that is practical and non-invasive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 13 publications
(27 reference statements)
8
33
8
1
Order By: Relevance
“…19 Linear vessels were detected in patients with CL at rates of 57% by Llambrich et al 4 and 53.8% by Yucel et al 5 In the present study, however, linear vessels were found in 26.0% (33/127) of lesions. 5 In the present study, by contrast, dotted vessels were detected at a rate of 24.4%. Thus, particular attention should be paid to the differentiation of KA, IEC, and SCC from CL because linear vessels may also occur in these conditions.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…19 Linear vessels were detected in patients with CL at rates of 57% by Llambrich et al 4 and 53.8% by Yucel et al 5 In the present study, however, linear vessels were found in 26.0% (33/127) of lesions. 5 In the present study, by contrast, dotted vessels were detected at a rate of 24.4%. Thus, particular attention should be paid to the differentiation of KA, IEC, and SCC from CL because linear vessels may also occur in these conditions.…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, no crust or ulcer develops in the middle. 5 In the present study, however, arborizing vessels (Fig. A keratin mass with small ulcers in the middle, and round, oval, or ellipseshaped targetoid keratin plugs that occur in the transitional phase of actinic keratosis to intraepidermal carcinoma were called red starburst-like patterns by Zalaudek et al 7 Although these resemble lesions of CL at this stage, the central keratin mass, low degree of ulceration and flatness of the lesions may be considered as differentiating factors.…”
Section: Discussionmentioning
confidence: 57%
“…Since erythema, hyperkeratosis and hairpin vessels can be observed in many dermatological conditions, they are not considered to be very useful or specific for diagnosing cutaneous leishmania [7]. However, the presence of a whitish starburst pattern was a strong indicator for cutaneous leishmaniasis in our patient.…”
Section: Discussionmentioning
confidence: 78%
“…Several dermoscopic findings have been described in cutaneous leishmaniasis, the most common ones include erythema, a large number of different vascular structures, white starburst-like patterns, central ulcers, yellow tears and hyperkeratosis [79]. Since erythema, hyperkeratosis and hairpin vessels can be observed in many dermatological conditions, they are not considered to be very useful or specific for diagnosing cutaneous leishmania [7].…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous leishmaniasis (CL) is a chronic infectious skin disease which has diverse clinical manifestations due to chronocity of the disease, host immune system, anatomical area of infection and age of the patient. The etiological agent of cutaneous leishmaniasis is Leishmania major and is transmitted to humans via Phlebotomus papatasi flies in the Old World and the Lutzomyia genus in the New World [2,3,[5][6][7][8]. After a bite, the lesions occur as inflammatory erythematous papules which further develop to nodules and crust in the center of the lesion [4,9,10].…”
Section: Introductionmentioning
confidence: 99%